Superoxide Is Produced by the Reduced Flavin in Mitochondrial Complex I: A SINGLE, UNIFIED MECHANISM THAT APPLIES DURING BOTH FORWARD AND REVERSE ELECTRON TRANSFER - Pryde, Kenneth R. (American Society for Biochemistry and Molecular Biology, 2011)
NADH:ubiquinone oxidoreductase (complex I) is a major source of reactive oxygen species in mitochondria and a contributor to cellular oxidative stress. In isolated complex I the reduced flavin is known to react with molecular oxygen to form predominantly superoxide, but studies using intact mitochondria contend that superoxide may result from a semiquinone species that responds to the proton-motive force (Δp) also. Here, we use bovine heart submitochondrial particles to show that a single mechanism describes superoxide production by complex I under all conditions (during both NADH oxidation and reverse electron transfer). NADH-induced superoxide production is inhibited by complex I flavin-site inhibitors but not by inhibitors of ubiquinone reduction, and it is independent of Δp. Reverse electron transfer (RET) through complex I in submitochondrial particles, driven by succinate oxidation and the Δp created by ATP hydrolysis, reduces the flavin, leading to NAD(+) and O(2) reduction. RET-induced superoxide production is inhibited by both flavin-site and ubiquinone-reduction inhibitors. The potential dependence of NADH-induced superoxide production (set by the NAD(+) potential) matches that of RET-induced superoxide production (set by the succinate potential and Δp), and they both match the potential dependence of the flavin. Therefore, both NADH- and RET-induced superoxide are produced by the flavin, according to the same molecular mechanism. The unified mechanism describes how reactive oxygen species production by complex I responds to changes in cellular conditions. It establishes a route to understanding causative connections between the enzyme and its pathological effects and to developing rational strategies for addressing them.